Introduction - Sablin, Ivan; Moniz-Bandeira, Egas (Planting parliaments in Eurasia, 1850-1950, 2021)
Parliaments are often seen as institutions peculiar to the Euro-American world. In contrast, their establishment elsewhere is frequently thought of as a derivative and mostly defective process. Such simplistic tales of unilateral and imperfect transfers of knowledge have led to a suboptimal understanding of non-Western experiences, as well as of their contribution to the shaping of the global political landscape of the modern world. As Eurasian parliaments often wielded rather limited powers, approaches departing from a normative Euro-American ideal have understood them as façade institutions. Contrary to the idea of parliamentarism being a belated transplant from European sources, one of the elements which made modern parliamentary institutions attractive was that they offered strong connections to the own past to those who adopted them. The existential problems faced by these empires meant that their newly formed parliamentary institutions were predominantly aimed at strengthening the state or reorganizing it from the perspective of the political elites.
Gesehen am 28.06.2021